Profiling Out-of-School Youth as Basis for Developing Effective Community Extension Programs - Millondaga, Reynold; Samillano, Dexter; Domingo, Bebeth; Yumen, Nelmer; Capague, Sara Jane; Arzaga, Tweetums Boe; Sebastian, Jerald; Elizan, Glofe Joy; Domingo, Angel Love; Dela Vega, Ma. Leizyl; Alvarado, Samantha Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to profile out-of-school youth (OSY) in the Municipality of Barbaza, Antique, Philippines and identify the factors affecting their non-enrollment as a basis for developing responsive community extension programs. The study was anchored on Bronfenbrenner’s Ecological Systems Theory and guided by the Input–Process–Output (IPO) Model. A descriptive research design was employed to determine the demographic characteristics of out-of-school youth and the factors contributing to their educational disengagement. Data were collected using a validated researcher-made survey questionnaire administered to 818 identified out-of-school youth aged 11–24 years through total enumeration sampling. Frequency, percentage, and weighted mean were used to analyze the data. The findings revealed that most respondents were male, aged 16–18 years, single, had reached the high school level, and were employed. Financial constraints emerged as the most significant factor affecting non-enrollment, followed by employment opportunities, family responsibilities, and lack of interest in schooling. These results indicate that socioeconomic challenges remain the primary barriers to educational participation among out-of-school youth. The study further found that many respondents discontinued their education during secondary schooling and entered employment or livelihood activities due to economic necessity. Overall, educational disengagement was largely influenced by financial limitations, employment demands, and family-related obligations. The study concludes that addressing the educational and socioeconomic needs of out-of-school youth requires responsive interventions that combine educational support, skills development, livelihood opportunities, and youth empowerment initiatives. Based on the findings, the SIGLA (Skills and Innovation for Growth, Livelihood and Advancement of Barbaza Out-of-School Youth) Program was proposed to enhance employability, financial literacy, and community participation among beneficiaries. The study supports Sustainable Development Goals (SDGs) 4, 8, and 10 by promoting educational inclusion, employability, and reduced inequalities. It also contributes to educational, socioeconomic, community, and institutional sustainability through evidence-based community extension programming.